Community Empowerment through Strengthening Islamic Educational Institutions: A Study on the Slopes of Mount Telomoyo - Muh Saerozi; Suwardi; Sri Marwiyati; HIdayatulloh, M. Agung (INFERENSI: Jurnal Penelitian Sosial Keagamaan, 2024)
The community on the slopes of Mount Telomoyo, which is far from the city, has its own uniqueness. Mutual cooperation among the community is always carried out to solve community problems. The community has established a complete basic education, both formal and non-formal. However, education that has a strategic role in regional development still has a gap between community expectations and reality. The gaps include the unequal participation of the community and the lack of cooperation between educational institutions. This study aims to provide strengthening of Islamic education in order to empower the community on the slopes of Mount Telomoyo. This study uses a Participatory Action Research (PAR) approach by involving the community to solve educational problems on the slopes of Mount Telomoyo. The results of the study show that the community agree on the need for integration of Islamic educational institutions as a short-term strengthening plan. The integration of KB/TK-MI-Madin steps include the alignment of the Islamic Religious Education curriculum, flipped cooperation of learning and evaluation, shared use of teacher books and student books, issuance of learning achievement certificates, issuance of decrees (SK) and implementation. This study provides implications for stakeholders on the slopes of Mount Telomoyo to provide policy and facilities support. Furthermore, community empowerment through strengthening Islamic educational institutions is discussed in this article.